A case of cavernous skull hemangioma of the frontal bone: Imaging features and diagnostic importance - Kocharlakota , Sridhar VNS; Tetta, Venkata Sarma Jayant; Aaqil Khan, Mohammed; Reddy, T Hruthika; Seelamonthula, Vaibhav Sai; Mohan, Vedhavarshini (Indian Journal of Case Reports, 2026)
Skull hemangiomas are rare, benign vascular tumors that account for